Inter-Municipal Cooperation in the Development of Industrial Parks and Tax Redistribution: The Road to Hell is Paved with Good Intentions - Razin, Eran (Quaestiones Geographicae, 2016)
Inter-municipal cooperation mechanisms have been promoted as flexible tools, reflecting the transition from government to governance in a new network economy and eliminating the need to engage in redrawing clear-cut boundaries in the context of soft spaces with fuzzy boundaries. An evaluation of inter-municipal cooperation in the development of industrial parks and tax revenue redistribution in Israel, from the first 1992 initiative to imposed redistribution in 2014/15, reveals how an initiative ’from below’ has been adopted and encouraged ’from above’, finally used by the central state as a tool of control, to serve its own objectives. It highlights the inherent temptation for top-down imposition, embedded in bottom-up cooperation mechanisms, calling for light-touch regulatory legislation and opting for gently imposed solutions where needed.